Design of a hybrid model for dynamic engagement behaviour analysis in a cloud-based environment. (2017) - Chen, You-Shyang; Lin, Chien-Ku; Chuang, Huan-Ming; Cheng, Ming-Chang
Taiwan Plurkers on Education and Technology @Facebook (TPET) is Taiwan's largest and most popular Facebook-based virtual community and aims to provide a platform for teachers to exchange, discuss and share knowledge. Therefore, it is essential to investigate ways to facilitate active engagement behaviour of members to obtain benefits with the greatest potential. This study identifies information system (IS) characteristics as triggers to explore the dynamic and iterative nature of engagement behaviour by multi-criteria decision-making (MCDM) analysis. Under the principle of a theoretical saturation, 14 active TPET members were interviewed in depth to investigate the dynamic relationship among dimensions and factors related to IS characteristics and engagement behaviour. The main findings can provide helpful guidance for TPET managers' decision-making regarding the enhancement of members' engagement behaviour and promotion of the sustainable development of the community, and ultimately improve the quality of teaching to create more innovative educational value for students.